Green transformational leadership and employees’ green behavior: a cross-level moderated mediation study - Cao, Jianwei; Sun, Haoxiang; Cao, Xulei; Ma, Haoran (Frontiers in Psychology, 2026)
Employees’ green behavior directly contributes to corporate environmental sustainability and generates positive spillover effects on society that support broader green transformation. As a leadership style that encourages employees’ pro-environmental actions, green transformational leadership has attracted growing scholarly attention. However, the mechanisms through which green transformational leadership shapes employees’ green behavior remain underexplored. Drawing on social learning theory and affective events theory, this study developed a cross-level theoretical model linking green transformational leadership and employees’ green behavior. Using Mplus, multilevel analyzes on matched data from 325 employees nested within 53 teams were conducted. The results indicated that (1) green transformational leadership was positively related to employees’ green behavior; (2) employees’ environmental passion mediated the relationship between green transformational leadership and employees’ green behavior; (3) pro-environmental organizational climate negatively moderated the mediating effect of employees’ environmental passion on the relationship between green transformational leadership and employees’ green behavior, such that the indirect effect is weaker when the organizational climate is more strongly pro-environmental. These findings enhance understanding of the mechanisms through which green transformational leadership shapes employees’ green behavior and offer practical implications for leveraging leadership to promote pro-environmental actions in organizations.